2015
DOI: 10.1097/qad.0000000000000814
|View full text |Cite
|
Sign up to set email alerts
|

Frequent nevirapine resistance in infants infected by HIV-1 via breastfeeding while on nevirapine prophylaxis

Abstract: Objective Assess nevirapine (NVP) resistance in infants who became infected in the three arms of the Breastfeeding, Antiretrovirals, and Nutrition (BAN) study: daily infant NVP prophylaxis, triple maternal antiretrovirals (ARV), or no extra intervention for 28 weeks of breastfeeding. Design Prospective cohort study. Methods The latest available plasma or dried blood spot specimen was tested from infants who became HIV-positive between 3 and 48 weeks of age. Population sequencing was used to detect mutation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 17 publications
1
11
0
Order By: Relevance
“…The prevalence of NVP-associated mutations in our cohort is within the range of previous studies involving children who had been exposed to single-dose or extended-NVP prophylaxis, 27% [13] to 60% [3,14,15]. However, previous studies of single-dose NVP involved younger children and demonstrated that resistance decayed to clinically insignificant levels in most infants by 12 months [2,3,911].…”
Section: Discussionsupporting
confidence: 71%
“…The prevalence of NVP-associated mutations in our cohort is within the range of previous studies involving children who had been exposed to single-dose or extended-NVP prophylaxis, 27% [13] to 60% [3,14,15]. However, previous studies of single-dose NVP involved younger children and demonstrated that resistance decayed to clinically insignificant levels in most infants by 12 months [2,3,911].…”
Section: Discussionsupporting
confidence: 71%
“…28,29 However, nevirapine has a low barrier to the selection of resistance and high proportions of viral resistance have been reported when there is regimen failure resulting in transmission. 30,31 Our data illustrate the potential danger of treating infants receiving nevirapine with rifampicin and underscore the importance of using isoniazid for TB prophylaxis in this population.…”
Section: Discussionmentioning
confidence: 78%
“…17 Some previous studies have already revealed that widespread use of preemptive therapy with anti-viral drugs could be generally suspected as ine cient, because certainly increase risk factors of multi-drug resistance and epidemic infections. [18][19][20] As far as considering severity and mortality rates for FIP at onset, potential epidemic of multi-drug resistant strains must be a great threat for us. Therefore, we are highly con dent that Mutian X should be administered selectively to the FIP subjects possible to get certain therapeutic effects, leading to a variety of bene ts on the cats and their owners.…”
Section: Discussionmentioning
confidence: 99%